On the sluggish response of prices to money in an inventory-theoretic model of money demand - Alvarez, Fernando 1964-; Atkeson, Andrew 1961-; Edmond, Chris (National Bureau of Economic Research, 2003)
We exposit the link between money, velocity and prices in an inventory-theoretic model of the demand for money and explore the extent to which such a model can account for the short-run volatility of velocity, the negative correlation of velocity and the ratio of money to consumption, and the resulting stickiness' of the aggregate price level relative to a benchmark model with constant velocity. We find that an inventory-theoretic model of the demand for money is a natural framework for understanding these aspects of the dynamics of money, velocity and prices in the short run.